SISTEM INFORMASI KULINER KOTA SALATIGA BERBASIS GEOGRAPHIC INFORMATION SYSTEM MENGGUNAKAN TEKNOLOGI LEAFLET - Michael Shawn Azaria; Ramos Somya (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Abstract Salatiga is a city called Indonesia Mini, this is because many students come from various regions in Indonesia to continue their education in the city of Salatiga. Sometimes many of them choose to stay in Salatiga when their education period is over. The large number of overseas students in Salatiga made several people take the initiative to open a food stall that sells regional specialties. More and more regional specialties are sold in Salatiga, resulting in a richer culinary diversity. Because there are so many culinary delights scattered in Salatiga, the problem that usually arises is the lack of information about the location of the typical Salatiga culinary. Therefore, this study aims to create an application based on a Geographic Information System (GIS) to inform culinary locations in Salatiga using the CodeIgniter framework, Leaflets to display maps on the application, and database storage using MySQL with the PhpMyAdmin feature in it. Keyword: Geographic Information System, CodeIgniter, GIS, Leaflet, Salatiga Culinary